Global adjustment for the Gravity Calibration Line Madrid-Valle de los Caidos - Camacho, A. G.; Ortíz, E.; Vieira, R. (Física de la Tierra, 2002)
A gravity difference of 121 mGal is to be found on the Madrid-Valle de los Caídos gravimetric calibration line, which is formed by 16 stations and streches 60 km from Madrid to the north western mountains. The line includes two absolute gravity stations, one in each terminal zone and both repeatedly observed (1989, 1992, 1994, 1997) by absolute meter, giving an absolute scale reference. Moreover, large continuous gravity records in each terminal zone provide empirical models for tidal response. This paper gives additional details about the calibration line and presents the adjustment process carried out for the gravity data bank obtained from 1979 with a total of 16 relative meters. Adjusted gravity values for the stations of the line are obtained with a standard deviation of around 7 µGal. Furthermore, the fit process provides instrumental parameters such as drift factors, scale factor and recording jumps for the meters in question.